Identification of Australian Aboriginal and Torres Strait Islander Cancer Patients in the Primary Health Care Setting - de Witt, Audra; Cunningham, Frances C.; Bailie, Ross; Bernardes, Christina M.; Matthews, Veronica; Arley, Brian; Meiklejohn, Judith A.; Garvey, Gail; Adams, Jon; Martin, Jennifer H.; Walpole, Euan T.; Williamson, Daniel; et al. (Frontiers in Public Health, 2017)
Background Aboriginal and Torres Strait Islander Australians have poorer cancer outcomes and experience 30% higher mortality rates compared to non-Indigenous Australians. Primary health care (PHC) services are increasingly being recognized as pivotal in improving Indigenous cancer patient outcomes. It is currently unknown whether patient information systems and practices in PHC settings accurately record indigenous and cancer status. Being able to identify Indigenous cancer patients accessing services in PHC settings is the first step in improving outcomes. Methods Aboriginal Medical Centres, mainstream (non-Indigenous specific), and government operated centres in Queensland were contacted and data was collected by telephone during the period 2014 to 2016. Participants were asked to: (i) identify the number of patients diagnosed with cancer attending the service in the previous year; (ii) identify the Indigenous status of these patients and if this information was available; (iii) how this information was obtained. Results Ten PHC centres across Queensland participated in this study. Four centres were located in regional areas, three in remote areas and three in major cities. All participating centres reported ability to identify Indigenous cancer patients attending their service and utilizing electronic Patient Care Information Systems (PCIS) to manage their records, however not all centres were able to identify Indigenous cancer patients in this way. Indigenous cancer patients were identified by PHC centres using PCIS (n=8), searching paper records (n=1), combination of PCIS and staff recall (n=1). Six different types of PCIS were being utilized by participating centres. There was no standardized way to identify Indigenous cancer patients across centres. Health service information systems, search functions and capacities of systems, and staff skill in extracting data using PCIS varied between centres. Conclusion It is crucial to be able to easily identify Indigenous cancer patients accessing health services in the PHC setting to monitor progress, improve and evaluate care, and ultimately improve Indigenous cancer outcomes. It is also important for PHC staff to receive adequate training and support to utilize PCISs efficiently and effectively.